FOREST FRAGMENTATION ANALYSIS BASED ON LAND COVER CLASSIFICATION USING OBJECT BASED IMAGE ANALYSIS (OBIA) IN CORRIDOR AREA OF MOUNT SIMPANG, WEST JAVA - Saefulloh, Sony
High connectivity along with compact and unfragmented forest area is an ideal condition for animal corridors. If fragmented, forest connectivity will decrease and will caused disturbed mobility of animals. ..... connects Mount Simpang and Mount Tilu. At present, information about the condition of forest as a connection between the two nature reserves has not yet known. This study aims to determine the level of forest fragmentation and condition of forest connectivity based on land cover conditions in the corridor area. The land cover of the mapping results is determined through object-based image classification (OBIA) using eCognition Developer software. The accuracy of land cover classification is determined using overall accuracy test and kappa accuracy Test. Determination of forest fragmentation and forest connectivity conditions are analyzed by using the Fragstats 4.2 software. Correlation Length Index (CLI) and Interspersion Juxtaposition Index (IJI) are the parameter used to analyze the conditions of forest connectivity. Forest fragmentation is analyzed by using six parameters including the number of patch (NP), patch density (PD), total edge (TE), edge density (ED), average patch area (Area_MN), and average patch shape index (Shape_Index). Afterward, weighting is used to determine the level of forest fragmentation. The classification results show that there are seven land cover consist of forest (245.15 ha), built area (0.56 ha), river (1.02 ha), shrubs (121.62 ha), agricultural land (18.15 ha), tea gardens (2.17 ha), and open land (2.03 ha) with overall accuracy of 90.52% and kappa accuracy of 87.98%. Forest connectivity has patches that tend to be clumped (IJI = 20.64%) and has a connectedness distance (CLI) of 503.73 m. Fragmentation in the corridor forest has NP = 1,293, PD = 330.9 / 100 ha, TE = 397.44 km, ED = 1,017.14 m / ha, Area_MN = 0.18 ha, and Shape_Index = 1.5, addressing that the level of forest fragmentation is very high.